Ophthalmic patients on antithrombotic drugs: a review and guide to perioperative management. Issue 8 (25th November 2014) - Kong, K-L; Khan, J
Abstract : The changing profile of patients undergoing ophthalmic surgery, with an increase in prevalence of antiplatelet and anticoagulant drug use, predisposes to bleeding complications. This mandates an awareness of these agents, allowing optimal patient management. We review traditional and newer agents in the context of cataract, vitreoretinal, glaucoma and oculoplastic surgery. Recommendations are given for continuation, cessation and re-commencement of these agents in order to minimise the risk of bleeding and thrombotic/thromboembolic complications.